Revisting the roles of progesterone and allopregnanolone in the nervous system: resurgence of the progesterone receptors - Schumacher, M. (2014)
Progesterone is commonly considered as a female reproductive hormone and is well-known for its role in pregnancy. It is less well appreciated that progesterone and its metabolite allopregnanolone are also male hormones, as they are produced in both sexes by the adrenal glands. In addition, they are synthesized within the nervous system. Progesterone and allopregnanolone are associated with adaptation to stress, and increased production of progesterone within the brain may be part of the response of neural cells to injury. Progesterone receptors (PR) are widely distributed throughout the brain, but their study has been mainly limited to the hypothalamus and reproductive functions, and the extra-hypothalamic receptors have been neglected. This lack of information about brain functions of PR is unexpected, as the protective and trophic effects of progesterone are much investigated, and as the therapeutic potential of progesterone as a neuroprotective and promyelinating agent is currently being assessed in clinical trials. The little attention devoted to the brain functions of PR may relate to the widely accepted assumption that non-reproductive actions of progesterone may be mainly mediated by allopregnanolone, which does not bind to PR, but acts as a potent positive modulator of γ-aminobutyric acid type A (GABA(A) receptors. The aim of this review is to critically discuss effects of progesterone on the nervous system via PR, and of allopregnanolone via its modulation of GABA(A) receptors, with main focus on the brain.